The role of foreign institutional investors in restraining earnings management activities across countries - Lel, Ugur (Journal of International Business Studies, 2019)
This study investigates the role of foreign institutional investors (FIIs) in restraining earnings management activities of firms under varying levels of investor protection. Firms manage their earnings less when independent FIIs are among their shareholders, especially for firms in which monitoring is more valuable – firms in weak investor protection countries and when firms have greater growth opportunities. These effects are robust to a quasi-exogenous shock to FIIs’ shareholdings, unobserved firm heterogeneity, and alternative earning management measures. FIIs are associated with an increase in foreign director presence on corporate boards and audit committees.